The Impact of Flexible Work Environment on Employee Productivity: A Survey Study at Zain Iraq Telecommunications Company - Ali, Asrar Abdulzahra (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to explore the impact of a flexible work environment on employee productivity through a survey-based approach conducted at Zain Iraq Telecom Company. The problem of this research is to attempt to answer the main question: How does a flexible work environment affect employee productivity at Zain Iraq Telecommunications Company? To address this problem, a main hypothesis was developed: There is a statistically significant relationship between a flexible work environment and increased employee productivity at Zain Iraq Telecommunications Company. The importance of this research lies in its ability to help Iraqi institutions and startups understand the advantages and challenges of flexible work, enabling them to make strategic decisions that support productivity and improve the work environment. The research adopts a descriptive-analytical methodology to understand the relationship between flexible work arrangements—such as remote work and flexible hours—and the level of employee performance and satisfaction. A random sample of 174 employees from various departments was selected, encompassing both those working under flexible systems and those under traditional work hours, to enable a comparative analysis. Data was collected using a structured questionnaire covering three dimensions: demographic characteristics, the use and perception of flexible work arrangements, and self-reported productivity levels. Data analysis was performed using SPSS, applying descriptive statistics, correlation analysis, and multiple regression to determine the effect of work flexibility on productivity. Results revealed a strong positive relationship between flexible work environments and increased employee productivity, as well as enhanced work-life balance and job satisfaction. However, some concerns were noted regarding communication among team members in remote settings, suggesting the need for improved communication strategies and managerial support. The study concludes that implementing flexible work models can significantly boost productivity and employee well-being if properly managed and recommends that organizations invest in infrastructure and training to maximize the benefits of flexible work systems.